Fear of communicating fear versus fear of terrorism: A human rights violation or a sign of our time? - Anyanwu, Chika (International Journal of Speech-Language Pathology, 2018)
At its very first session, the United Nations General Assembly, adopted Resolution 59(I) which states that “freedom of information is a fundamental human right and … the touchstone of all the freedoms to which the United Nations is consecrated”. In 1948, it proclaimed the Universal Declaration of Human Rights in Paris. Article 19 of that Declaration states that “everyone has the right to freedom of opinion and expression; this right includes freedom to hold opinions without interference and to seek, receive and impart information and ideas through any media and regardless of frontiers”. When we place these basic human rights against current global terror threats, and consequent restrictive antiterror legislations to combat them, the question becomes whether Article 19 is still relevant in the context of today’s changed security landscape. The aim of this paper is to explore ways that anti-terror legislations can balance between national security, and the protection of freedom of information.